1990
DOI: 10.3354/meps059221
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic differences between Baltic and North Sea populations of Mytilus edulis evaluated through reciprocal transplantations. III. Physiology

Abstract: Mussels Mytilus edulis L., aged 1 yr, were transplanted from a low saline regime (6 to 7 %o S, northern Baltic proper) to a high saline regime (20 to 30 %O S, North Sea). Physiological responses of these mussels, after 1 mo and 1 yr of acclimatisation, were compared to those of native North Sea mussels and allele frequencies for 2 polymorphic loci (Pgi and Pgm) in the populations were scored.Oxygen consumption, ammonia excretion, 0 / N ratios, and clearance rate of transplanted Baltic mussels approached those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…Enzyme analysis by Johannesson et al (1990) showed that the high initial mortality of North Sea mussels transplanted to the Baltic was selective in some enzyme loci and that only North Sea mussels of Baltic Sea genotype survived. Also the sudden mortality of Baltic mussels in late summer 1 yr after transplantation to the North Sea seems to be due to genetic factors, as it was very selective against Baltic genotypes (Johannesson et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Enzyme analysis by Johannesson et al (1990) showed that the high initial mortality of North Sea mussels transplanted to the Baltic was selective in some enzyme loci and that only North Sea mussels of Baltic Sea genotype survived. Also the sudden mortality of Baltic mussels in late summer 1 yr after transplantation to the North Sea seems to be due to genetic factors, as it was very selective against Baltic genotypes (Johannesson et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Thus we conclude that the main reason for the much lower growth rate is likely to be a salinity-dependent change in amino acid metabolism and nitrogen excretion resulting in a less favorable energy balance in low saline areas (Tedengren & Kautsky 1986) (cf. also di.scussion in Tedengren et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations